The Affective Revolution in Entrepreneurship: An Integrative Conceptual Review and Guidelines for Future Investigation - Portocarrero, Florencio F.; Newbert, Scott L.; Young, Maia J.; Zhu, Lily Yuxuan (Journal of Management, 2025)
Entrepreneurial affect has emerged as a burgeoning area of study, with a wealth of articles demonstrating that affect, broadly conceptualized, plays an important part in entrepreneurial life. While a few affective phenomena, such as passion and positive and negative affect, are primarily driving the affective revolution in entrepreneurship, a wide range of additional forms of affect, from momentary feelings to enduring affective dispositions, have been found to influence entrepreneurs’ judgments, decision-making, attitudes, and behaviors in distinct parts of the entrepreneurial process. Moreover, entrepreneurs’ affective experiences and displays of these experiences influence entrepreneurial behaviors and investors’ decision-making. Although this is an exciting time for work on entrepreneurial affect, several theoretical and empirical inconsistencies impede further knowledge accumulation. To assess how and why affect is critical to entrepreneurship, to clarify the theoretical inconsistencies, and to provide an integrative framework, we conduct a systematic review of 276 published empirical and conceptual articles on entrepreneurial affect. In doing so, we analyze how various affective phenomena (e.g., emotions, moods, sentiments), along with their discrete forms (e.g., anger, grief, happiness), influence and are influenced by specific stages of the entrepreneurial process. We conclude that while this body of research confirms that entrepreneurship is an emotional endeavor, the collective approach has thus far obscured a more detailed and useful understanding of affect in each stage of the entrepreneurial process. We examine the theoretical and empirical approaches taken to date and lay out an agenda for future scholars, thus bolstering the affective revolution in entrepreneurship.